Determinants of the theory of planned behavior of consumer related to intention to purchase of organic vegetables (Bioscience Journal, 2019)
The Brazilian consumers have expanded their purchases of organic products. However, little is known about these consumers’ purchase behavior. Considering the Theory of Planned Behavior, was aimed at this study to evaluate the positive influence of attitude, subjective norms and perceived behavior control in the decision to buy organic vegetables and to evaluate the causal relationships of these variables in the intention to buy vegetables in function of the sociodemographic characteristics of the consumer. During the purchase process, 472 people were interviewed using a questionnaire. The structural equation modeling with the partial least squares method was used to test the relationships proposed in the specific objectives, among the latent variables, attitude, subjective norm, perceived control and uncertainty, predictive of purchase intention. The results indicate that the latent predictive variables influence positively the intention to purchase, unless the perceived uncertainty that the higher this is, the less will be the intention to purchase. Regarding the socioeconomic variables, only the groups targeted in the level of schooling and family income showed significant differences for the relationship between the subjective norms and purchase intention, and for the group age range, the relation between perceived uncertainty and purchase intention.